Cyclodextrin Monomers and Polymers for Drug Activity Enhancement - Matencio, Adrián (Polymers (Basel), 2021)
Cyclodextrins (CDs) and cyclodextrin (CD)-based polymers are well-known complexing agents. One of their distinctive features is to increase the quantity of a drug in a solution or improve its delivery. However, in certain instances, the activity of the solutions is increased not only due to the increase of the drug dose but also due to the drug complexation. Based on numerous studies reviewed, the drug appeared more active in a complex form. This review aims to summarize the performance of CDs and CD-based polymers as activity enhancers. Accordingly, the review is divided into two parts, i.e., the effect of CDs as active drugs and as enhancers in antimicrobials, antivirals, cardiovascular diseases, cancer, neuroprotective agents, and antioxidants.